Overview of doctrinal studies of the human rights phenomenon in the Ukraine. Human rights and public administration: Collective monograph - Kovbas, Ihor (Angel Kanchev University of Ruse, 2022)
Considering the problematic issues related to human rights that have emerged, reflected in national philosophical thought, political views and enshrined in the legal prescriptions of the state, which occurred in the territory of Ukraine, from our point of view, it is appropriate to study the genesis of human rights in the modern existence of Ukrainian society and its state. To be specific, the purpose of this article is to deeply explore the subject matter of transforming and adapting the historical and world doctrine of human rights in Ukraine as a social, political-state formation, i.e. to investigate how the objectification of human rights in civil-political and legal life of Ukrainian society and its state was carried out.
Keywords: vitality; sociality; As noted by scientists; humanisation of man